2015
DOI: 10.1101/019323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Multi-allelic Genetic Architecture of a Variance-heterogeneity Locus for Molybdenum Accumulation Acts as a Source of Unexplained Additive Genetic Variance

Abstract: Most biological traits are regulated by both genetic and environmental factors. Individual loci contributing to the phenotypic diversity in a population are generally identified by their contributions to the trait mean.Genome-wide association (GWA) analyses can also detect loci based on variance differences between genotypes and several hypotheses have been proposed regarding the possible genetic mechanisms leading to such signals. Little is, however, known about what causes them and whether this genetic varia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…To extrapolate these 256 findings to the genome level, the proportions of all evaluated predictor pairs that 257 displayed these patterns were calculated and then multiplied with the total number of 258 possible cis-cis/cis-trans/trans-trans pairs in the genome (Table S1). an earlier study of this dataset (Forsberg et al 2015), it was revealed that a large 270 . CC-BY 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…To extrapolate these 256 findings to the genome level, the proportions of all evaluated predictor pairs that 257 displayed these patterns were calculated and then multiplied with the total number of 258 possible cis-cis/cis-trans/trans-trans pairs in the genome (Table S1). an earlier study of this dataset (Forsberg et al 2015), it was revealed that a large 270 . CC-BY 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
mentioning
confidence: 78%
“…How dependent is the prevalence of high order LD 307 and cis vs trans predictors on the population size? We also present an empirical 308 example where high order LD exists between a cis-trans predictor pair with 309 significant statistical epistasis and a locus displaying a strong genetic variance 310 heterogeneity due to independent contributions by multiple linked polymorphisms 311 (Forsberg et al 2015). This illustrates how complex inheritance patterns of individual 312 loci, something usually not explored in GWAS data, further complicates the 313 interpretation of detected statistical epistatic signals.…”
mentioning
confidence: 94%
See 3 more Smart Citations